Edukasi Pemilahan Sampah dalam Mengatasi Permasalahan Sampah Plastik di Tiban - Sumantika, Arsyad; Kornelis , Yudi; Riswandi, Riswandi; Tarigan , Elsya Paskaria Lodya (PUAN INDONESIA, 2025)
Through various educational and participatory activities, this community service program aims to increase awareness about waste management in the Tiban area. The aim of this activity is to increase public and local community awareness of the importance of waste sorting. The method used is outreach, namely socialization regarding waste sorting based on types such as organic, inorganic and dangerous waste, so that it can encourage the community to actively participate in activities in maintaining environmental cleanliness. The results of this service show that the Tiban community understands and is more involved in more efficient waste management, supported by adequate facilities. It is hoped that this program can create a more efficient and sustainable waste management system in the Tiban area and give local communities the opportunity to adopt a similar waste processing system. This can help preserve the environment in the long term.